STANCE EXPRESSIONS PADA KANAL MILD REPORT SITUS BERITA TIRTO.ID: ANALISIS LINGUISTIK KORPUS - Muhammad Rahmat Alimuddin*; Gusnawaty Gusnawaty*; Andi Agus Salim* (Jurnal Edukasi Khatulistiwa : Pembelajaran Bahasa dan Sastra Indonesia, 2022)
AbstractThis study aims to determine the expression of attitudes on the Mild Report news site Tirto.id. Stance expressions are the author's feelings and personal thoughts. This research uses the corpus linguistics method. The analysis of the corpus and computer data was carried out using the AntConc software. The data were analyzed using Hyland's stance expressions analysis framework. Namely, it consists of four elements, namely hedges, boosters, attitude markers, and self-mentions. The results showed that the attitude markers element was 24%, the boosters were 31%, the hedges element was 41%, and self mentions was 4%. This finding shows that the stance expressions of Hedges and Booster are used by the editorial team of Tirto.id respectively. Hedges points out that the author's decision to avoid a full commitment to the reinforcing statement expresses certainty about the proposition he makes in the text. Based on the research, it can be said that the writers of the Mild Report news on the Tirto.id website tend to be careful, such as by avoiding more risk, on the other hand the author also shows his confidence in the data based on the prepositions built by the author on the news text that is presented. This research can be developed further by adding the amount of data in the corpus, namely Mild Report news articles on the Tirto.id site. Stance expression analysis can also be applied to other texts, such as discourses or academic works to determine the author's attitude by utilizing the linguistic features of the text. Keywords: Stance expressions, Typical stance items, Corpus Linguistic, News Sites, Tirto.id.